Congenital poikiloderma with unusual hypopigmentation and acral blistering at birth (1999)
Congenital poikiloderma is an uncommon hereditary disorder. It has been reported in association with various synuromes. No case has previously been reported from this environment. We report a case of congenital poikiloderma in a two and a half year old female Nigerian associated with unusual generalised hypopigmentation and acral blisters at birth. The child subsequently developed macular hyperpigmentation on an erythematous background and atrophy of the skin. Although he had some features which were suggestive of Rothmund-Thomson syndrome (RTS), the presence of nypopigmentation at birth along with acral blistering, was noted to be peculiar to this child. We, therefore, feel that this case presents a distinct variant of congenital poikiloderma that has not been described previously.